Evaluating superelastic and shape memory effects using the photostress technique. (September 2020) - Adelfar, Masoumeh; Tavangar, Reza; Horandghadim, Nazila; Khalil-Allafi, Jafar
Graphical abstract: Highlights: For the first time superelastic property of NiTi was pursued by Photostress test Analysis results proved the concurrent presence of austenite and martensite at 20 °C Rising aging time boosted martensite value and subsequently reduced superelasticity Homogeneous and non-homegeneous deformation was followed by colorful patterns Reversible martensitic transformation in NiTi under stress was observed visually Abstract: Photostress is a photoelastic-based technique which has most widely been utilized for accurate measurement of the superficial stresses and strains, namely small elastic strains. In this study, the Photostress technique has been applied to assessing the superelastic and shape memory characteristics of NiTi alloy. To this end, the NiTi alloy was aged at 450 °C for different times of 15, 25 and 40 min. and corresponding transformations were analyzed via differential scanning calorimetry (DSC) and X-ray diffraction (XRD) methods. Mechanical properties were also studied by the cyclic tensile test at room temperature. The results revealed the simultaneous presence of austenite and martensite phases in NiTi alloy at room temperature. The color patterns obtained from the Photostress technique were applied to interpreting the transformation under cyclic loading as well as the homogeneous and heterogeneous strain distribution of heat-treated specimens. The development of the existing phases during cyclic loading was characterized by the variations of the color patterns. Experimental results suggest that there is a great possibility of using the Photostress technique to study the superelastic behavior.